McGill Campus. Historical Development - Weiner, Michaela (Université McGill, 1979)
Keywords: Université McGill

McGill since 1920 - Yulen, Audrey (Université McGill, 1958)
Keywords: Université McGill

Étude patrimoniale des sites et des bâtiments hospitaliers reliés à l'Université McGill - Lachapelle, Jacques; Bisson, Pierre-Richard (1997)
Keywords: Hôpital Général; Hôpitaux; Royal Victoria Hospital

The Building of McGill University - Traquair, Ramsay (Journal, Royal Architectural Institute of Canada, 1925)
Keywords: Université McGill

George Heath MacDonald (Class of 1911): The Story of One Graduate from McGill University's School of Architecture - Johnson, Percy (Bulletin | Society for the Study of Architecture in Canada/Société pour l'étude de l'architecture au Canada, 1996)
Keywords: Université McGill

Teaching the History of Architecture at McGill, 1896-1903 - Schoenauer, Norbert (Bulletin | Society for the Study of Architecture in Canada/Société pour l'étude de l'architecture au Canada, 1996)
Keywords: Université McGill

The First Leaders of McGill's School of Architecture: Stewart Henbest Capper, Percy Nobbs, and Ramsay Traquair - Gournay, Isabelle (Bulletin | Society for the Study of Architecture in Canada/Société pour l'étude de l'architecture au Canada, 1996)
Keywords: Université McGill

Attention continue - Diodati, Giovanni (Continuité, 2016)
Keywords: Conservation; Université McGill

A Scout of the Past: Ramsay Traquair and the Legacy of the National Art Survey of Scotland in Quebec - Murray, Irena (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Université McGill; Écossais

'Archi-ettes' in Training: The Admission of Women to McGill's School of Architecture - Adams, Annmarie (Bulletin | Society for the Study of Architecture in Canada/Société pour l'étude de l'architecture au Canada, 1996)
Keywords: Femmes; Université McGill

"An Ocean of Noise": H.E. Reilley and the Making of a Legitimate Social Problem, 1911-45 - Rudy, Jarrett; Kenny, Nicolas; Fahrni, Magda (Journal of Canadian Studies / Revue d'études canadiennes, 2017)
Keywords: Physique; Université McGill

Looking Around: The Architecture of Medical Education - Adams, Annmarie (Transforming Medical Education: Historical Case Studies of Teaching, Learning, and Belonging in Medicine, 2022)
Keywords: Médecine; Université McGill

University Club de Montréal - Noppen, Luc (Les chemins de la mémoire. Monuments et sites historiques du Québec, 1991)
Keywords: Clubs; Patrimoine; Université McGill

Designing the Medical Museum - Adams, Annmarie (Healing Spaces, Modern Architecture, and the Body, 2018)
Keywords: Musées; Médecine; Université McGill

The Club Building / L'Édifice du Club - Drummond, Derek A. (University Club of Montreal, 1907-2007 / Le Club Universitaire de Montréal, 1907-2007, 2007)
Keywords: Clubs; University Club; Université McGill

The Design of the Peter Redpath Museum at McGill University: the Genesis, Expression and Evolution of an Idea about Natural History - Bronson, Susan D. (Université de Montréal, 1992)
Keywords: Musées; Redpath (musée); Université McGill

The Design of the Peter Redpath Museum at McGill University: The Genesis, Expression, and Evolution of an Idea About Natural History - Bronson, Susan (Bulletin | Society for the Study of Architecture in Canada/Société pour l'étude de l'architecture au Canada, 1992)
Keywords: Musées; Redpath (musée); Université McGill

Encountering Maude Abbott - Adams, Annmarie (Feminist Encounters: A Journal of Critical Studies in Culture and Politics, 2018)
Keywords: Abbott, Maude E.; Femmes; Histoire; Hôpitaux; Musées; Médecine; Royal Victoria Hospital; Université McGill

The Segregated City: Class and Occupation in Montreal 1861-1901/La ville différenciée: professions et classes sociales à Montréal, 1861-1901 - Lewis, Robert D. (Université McGill, Département de géographie, 1985)
Keywords: Locataires; Logement; Mobilité résidentielle

The McTavish Pumphouse - Maffini, Giulio (Université McGill, 1970)
Keywords: Aqueduc; Mont Royal

The Expansion of the University of Montreal in the 60' - Weiser, Fred (Université McGill, 1968)
Keywords: Université de Montréal

Transforming the Ideal: Visions and Revisions of Housing in a French-Canadian Community, 1942-1995 - Gilliland, Jason A. (Université McGill, 1996)
Keywords: Cité-Jardin du tricentenaire; Logement

Entre globalisation et réalités locales: centres commerciaux et formes urbaines à Los Angeles, Montréal et Paris / Between Globalization and Local Realities: Shopping Centers and Urban Forms in Los Angeles, Montreal and Paris - Moretti, GianPiero (Université McGill, 2004)
Keywords: Centres commerciaux

Design Considerations in Urban Low-Income Housing Redevelopment with Special Reference to Montreal - Chan, David Wai (Université McGill, 1970)
Keywords: Logement

Accessibility: A Performance Measure for Land-Use and Transportation Planning in the Montréal Metropolitan Region - Cerdá, Assumpta (Université McGill, 2009)
Keywords: Navettage

Industrial Land Retention in Two Cities: Municipal Strategies to Retain Manufacturing in Industrial Districts in Montreal and New York City - Charters, Stephen (Université McGill, 2011)
Keywords: Arrondissements; LaSalle; Le Sud-Ouest (arrondissement)

The Development of Complex Commercial Projects in Central Areas with Special Reference to Montreal - Ng, Spencer Che Lou (Université McGill, 1965)
Keywords: Gratte-ciel

Nature's Improvement Wildlife, Conservation, and Conflict in Quebec, 1850-1914 - Ingram, Darcy (Université McGill, 2007)
Keywords: Clubs; Faune; Montreal Hunt Club; Natural History Society

Residential Mobility in Montreal, 1861-1901 - Gilliland, Jason A. (Université McGill, 1993)
Keywords: Famille; Logement; Mobilité résidentielle

Redimensioning Montreal: Circulation and Urban Form, 1846-1918 - Gilliland, Jason A. (Université McGill, 2001)
Keywords: Incendies; Port; Rues

Cyclist Injury Risk and Pollution Exposure at Urban Signalized Intersections - Strauss, Jillian (Université McGill, 2012)
Keywords: Cyclisme; Pollution

St. Lawrence Blvd. as "Third City": Place, Gender and Difference along Montréal's "Main" - Podmore, Julie (Université McGill, 1999)
Keywords: Rues; Saint-Laurent (rue)

La contestation des espaces gais au centre-ville de Montréal depuis 1950 - Guindon, Jocelyn M. (Université McGill, 2001)
Keywords: Police; Quartiers

Salubrious Settings and Fortunate Families: The Making of the Golden Square Mile, 1840-1895 - MacLeod, Roderick (Université McGill, 1998)
Keywords: Anglophones; Golden Square Mile; Protestants; Quartiers

"Le Canada est un païs de bois": Forest Resources and Shipbuilding in New France, 1660-1760 - Delaney, Monique (Université McGill, 2003)
The colonial contribution to the French naval shipbuilding industry in the seventeenth and eighteenth centuries, explored within the context of the forest from which the resources for the industry were taken, was a remarkably successful venture that came to an end with the onset of war. In the past, the end of the French naval shipbuilding industry in New France has been attributed to the action or inaction of France that resulted in the inefficient use of forest resources. Issues of interest in, organization or support of colonial efforts by France, however, were nevertheless, limited by the immutable realities of the colonial forest environment. This thesis argues that the success of the industry, considered within the appropriate context, is a consequence of colonial persistence in the face of constraints imposed by the colonial forest environment---despite these other significant issues. The official correspondence, written by colonial officials in New France, record colonial efforts to supply France with timber and detail the development of a naval shipbuilding industry in the colony. These documents provide source material for a case study that demonstrates the constraints imposed by the colonial forests on the experience of colonists, timber suppliers and shipbuilders. The colonial forest was not the same as the forests in France. A simple transfer of knowledge and practice from one forest to another was insufficient to deal with the differences in climate, forest age, tree species and the extent to which human activity affected the different forests. These differences challenged the way in which colonists could use forest resources for their own needs, for export to France and for naval construction. To consider this use of resources, without considering the differences between the available materials in the colony and those available in France, is to look at the story removed from the setting in which it took place. The unique forest in the colony was the setting in which colonial shipbuilding took place. Any study of the development of this industry, or any other industry that relied on forest resources, must give consideration to the constraints and realities of that forest.
Keywords: Construction navale

The Segregated City: Residential Differentiation, Rent and Income in Montreal, 1861-1901 - Lewis, Robert D. (Université McGill, 1985)
Keywords: Locataires; Logement; Mobilité résidentielle

The Civil Architecture of John Ostell - James, Ellen S. (Université McGill, 1983)
Keywords: Arpenteurs; Ostell, John

The Montreal Villa, 1830 to 1930 - Jooste, Johan K. (Université McGill, 1985)

The Evolution of Montreal's Precipitation: Climate - Leduc, Richard (Université McGill, 1977)
Keywords: Climat

The Physical Characteristics of Suburban Development with Special Reference to the Lakeshore Communities of Montreal - Gibbs, Phillip F. (Université McGill, 1971)
Keywords: Banlieue; West Island

The Evolution of Commercial Land Use in Cities, with Special Reference to Montreal - Auyang, Antonio Chak War (Université McGill, 1965)

Street Patterns in Residential Areas with Special Reference to Montreal - Li, Ying H. (Université McGill, 1965)
Keywords: Rues

A Study of the Relationship between Ecological and Non-Ecological Factors in the Development of Certain Natural Areas of Montreal - Richardson, Nigel H. (Université McGill, 1954)
Keywords: Notre-Dame-de-Grâce; Quartiers; Rosemont; Snowdon

The Relationship between Landscape and Residential Growth Patterns: The Example of Western Montreal Island - Bridger, M. Keith (Université McGill, 1964)
Keywords: West Island

Evolution of Patterns of Land Subdivision with Special Reference to Montreal - Khor, Ean (Université McGill, 1964)

City Squares and Open Spaces with Special Reference to Montreal - Hoffman, Andrew (Université McGill, 1962)
Keywords: Places publiques; Squares

Making and Using Environmental Information: An Analysis of the Development and Use of Two GIS Tools for Public Environmental Engagement - Klinsky, Sonja (Université McGill, 2004)
Keywords: West Island

Montreal Up in Smoke: A Spatial Analysis of Mid-Nineteenth Century Urban Fires - Spencer, Pheobe (Université McGill, 2011)
Keywords: Incendies

Privacy in Homes of Shaamy Muslim Immigrants: A Study of Privacy Patterns in Single-Family Detached Homes and Townhouses of Middle-Class Immigrants in Montreal - Hallak, Mahmoud Essam (Université McGill, 2000)
Keywords: Musulmans; Syriens

The Natural Areas of the Montreal Metropolitan Community with Special Reference to the Central Area - Zatuka, Leo (Université McGill, 1948)
Keywords: Parcs

Climate Change Adaptation and Mitigation through Urban Agriculture: A Montreal Case Study - Lebedeva, Julia (Université McGill, 2008)
Keywords: Climat

Housing without Families: The Housing Situation of Non-Family Households in Montreal - Lavigne, Jean-François (Université McGill, 1988)
Keywords: Logement

Community Response to Environmental Change: A Case Study of Montreal's West Island 1981-1991 - Adams, Jennifer (Université McGill, 1992)
Keywords: Quartiers; West Island

A Comparison of Workforce Housing Practices in Three Cities and their Applicability to Montreal - Lazarovic, Rebecca (Université McGill, 2010)
Keywords: Logement; Travail

Rethinking Trench Expressways: Urban Design Strategies with Applications to Montreal's Décarie Autoroute - Richer, Nadia (Université McGill, 2010)
Keywords: Autoroutes

Montreal Electric Streetcar Suburbanization: A Study of a Canadian City’s Morphological Transformation Before World War 1 - Karczmar, Christine Elizabeth (Université McGill, 2013)
Keywords: Banlieue; Tramways

Effective Public Consultations and Follow-Ups? Evaluating Montréal’s Municipal Public Hearing Processes in Large-Scale Urban Developments - Aubin, Raphaëlle (Université McGill, 2010)
Keywords: Griffintown; Pointe-Saint-Charles; Quartiers

Homonormative Architecture & Queer Space: The Evolution of Gay Bars and Clubs in Montréal - Vallerand, Olivier (Université McGill, 2010)
Keywords: Alcool

The Physical Design of Alleys: An Evaluation of Alleys in the Montreal Plateau - Wise, David (Université McGill, 2004)
Keywords: Plateau Mont-Royal; Quartiers

Making Montreal's Indoor City Accessible for People with Disabilities - Hagg, Matthew (Université McGill, 2009)
Keywords: Espace souterrain

Movement, Morphology and Circulation of Montreal Summer Storms - Shaw, Roderick (Université McGill, 1970)
Keywords: Climat

Une étude bioclimatique de la ville de Montréal - Lafleur, Daniel (Université McGill, 1972)
Keywords: Climat

The Bias of Libraries: Montréal's Grande Bibliothèque - Mickiewicz, Paulina (Université McGill, 2013)
Keywords: Bibliothèque Saint-Sulpice; Bibliothèque centrale de Montréal; Bibliothèque nationale

Dynamics of Heavy Warm Season Precipitation Events in Montréal - Dookhie, Giselle C. (Université McGill, 2011)
Keywords: Climat

Visual Art/Public Art and Urban Development: A Case Study of Montreal (1967-1992) - Boyce, Margaret (Université McGill, 2001)
Keywords: Centre canadien d'architecture; Jardins; Squares

A Synoptic Climatology of Ground-Level Ozone for Montreal, Quebec - Stephens, Kate (Université McGill, 1995)
Keywords: Climat

A Synoptic Climatology of Montreal Precipitation - Fischer, Alexander P. (Université McGill, 1998)
Keywords: Climat

Climate and Architecture: With Special Reference to Montreal and Surroundings - Aronin, Jeffrey Ellis (Université McGill, 1951)
Keywords: Climat

Freezing Rain in the Montreal Area - Leech, Margaret E. (Université McGill, 1978)
Keywords: Climat

The Clustering of Skyscrapers with Special Reference to Montreal - Shank, Wesley Ivan (Université McGill, 1965)
Keywords: Gratte-ciel

The Petrology of a Part of Westmount Mountain near Summit Circle, Montreal - Malouf, Stanley Edward (Université McGill, 1936)
Keywords: Géographie physique

Planetary and Synoptic-Scale Analysis of Freezing Rain Events in Montreal, Quebec - Ressler, Gina (Université McGill, 2010)
Keywords: Climat

Recent Trends in Highrise Multiple House with Special Reference to the Rockhill Apartments, Montreal - Ghoshal, Prabhansu Kumar (Université McGill, 1969)
Keywords: Logement

Small Living Spaces: A Study of Space Management in Wartime Homes in Montreal - Pantelopoulos, Maria D. (Université McGill, 1993)
Keywords: Logement

The Evolution of Prefabricated Interior Components for Post-Occupancy Modification - Ou, Yangli (Université McGill, 1999)

Acoustics in Architectural Design: An Annotated Bibliography on Architectural Acoustics - Doelle, Leslie L. (Université McGill, 1964)

Preserving Old Buildings: Adaptive Use for Residential Purposes in Montreal - Vujadinovic, Milenko (Université McGill, 2002)
Keywords: Conservation; Patrimoine

Making the Creative City: A Case Study of the Quartier des Spectacles in Montreal - Loison, Laurie (Université McGill, 2013)
Keywords: Quartier des spectacles; Quartiers

New Urbanism in Practice: An Analysis of Five Greater Montreal Area Neighbourhoods - Vannelli, Jason (Université McGill, 2009)
Keywords: Griffintown; Quartiers; Rosemont; Saint-Laurent (ville); Île-des-Soeurs

Sky's the Limit: The Operations, Renovations and Implications of a Montréal Gay Bar - Allan, James (Université McGill, 1997)
Keywords: Alcool

[Re]Claiming Montreal’s Memory: Demolition and the Photography of Edith Mather - Southcott, Tanya (Université McGill, 2013)
Keywords: Patrimoine; Paysages; Photographie; Rues

Mixed Land Use Zoning with Special Reference to the Inner Cities of Montreal and New York City - Gumusyan, Garo (Université McGill, 1979)

Les fonctions politiques du centre culturel: La Place des Arts et la Révolution tranquille - Illien, Gildas (Université McGill, 1995)
Keywords: Place des Arts; Places publiques

The Summit of Distinguished Living: Montreal's Gleneagles Apartments - Havekes, Luke Henry (Université McGill, 2011)
Keywords: Golden Square Mile; Logement; Quartiers

Human Scale in the Urban Design of Montreal Residential Developments - Lucic, Katija (Université McGill, 1995)
Keywords: Anjou; Banlieue; Centre-sud (quartier); Quartiers; Rues; Squares

Industrial Land Use in Urban Areas with Special Reference to Montreal - Sharma, Brajesh Chander (Université McGill, 1971)

Outdoor Play Areas for Children in High-Density Housing in Montreal - Aggarwal, Monica (Université McGill, 2001)
Keywords: Enfants; Parcs; Plateau Mont-Royal; Quartiers

Privacy in Row Houses of Montreal - Rahbar, Mehrdad (Université McGill, 1996)
Keywords: Logement

The Changing Character of Streets in Central Areas with Special Reference to Sherbrooke Street as a Principal Street in City of Montreal-Canada - Rege, Ratan M. (Université McGill, 1966)
Keywords: Rues; Sherbrooke (rue)

Stewardship as Partnership: A Comparative Study of Positive Human-Environment Relationships in East Cree and Suburban Montreal Communities - Forrest, Margaret Anne (Université McGill, 2006)
Keywords: Banlieue; Parcs; Pointe-Claire

The Rebirth of the Shophouse in the Modern Age with a Special Reference to Montreal - Xu, Ti (Université McGill, 1998)
Keywords: Logement

Days and Nights: Class, Gender and Society on Notre-Dame Street in Saint-Henri, 1875-1905 - Lord, Kathleen (Université McGill, 2000)
Keywords: Quartiers; Rues; Saint-Henri

Blanche Lemco van Ginkel and H.P. Daniel van Ginkel: Urban Planning - Hodges, Margaret Emily (Université McGill, 2004)

A Survey of New Towns about Metropolitan Areas with Special Reference to Montreal - Kentridge, Leon R. (Université McGill, 1961)

A Survey of Industrial Estates with Special Reference to Montreal - Grasser, Otto (Université McGill, 1964)

A Study of Recreation in a Rapidly Developing Community in Montreal - Faughnan, Jeanne; Gabois, Denise; Miller, Robert; Ozier, Morris; Romer, Gabrielle; Sinuk, Morris (Université McGill, 1953)
Keywords: Quartiers; Saint-Laurent (quartier)

A Neighborhood that Empowers Women: In Search of Housing Sustainability - Insaf, Zeenat S. (Université McGill, 1999)
Keywords: Femmes; Logement

Coming into Site: Identity, Community and the Production of Gay Space in Montréal - Doyle, Vincent André (Université McGill, 1996)

Can Transit and Spatial Planning Synergy Work at the Regional Scale? Understanding Metropolitan Transit-Oriented Development Planning and its Challenges in the Canadian City-Regions of Toronto, Montreal and Vancouver - Hamzah, Muhammad Zulkarnain (Université McGill, 2013)
Keywords: Transport en commun

Development of Cote A Baron - Marshall, Robert S. (Université McGill, 1983)
Keywords: Baron (côte à)

Beyond the Decline: Revaluing Montreal's Movie Palaces - Heather Gibb, Alexandra (Université McGill, 2015)
Keywords: Cinéma; Conservation; Patrimoine

A Community of Believers and Healers: Learning from the functional characteristics of Hôtel Dieu - McDonald, Marie-Pierre (Université McGill, 2014)
Keywords: Communautés religieuses; Hôpitaux; Hôtel-Dieu

Shaping Time in the City: A Cultural History of Concrete Modernity in Montreal, 1903-2015 - Charles, Julia Morgan (Université McGill, 2015)
Keywords: Autoroutes; Béton; Port; Stade olympique

Industry and Space: the Making of Montreal's Industrial Geography, 1850-1918 - Lewis, Robert D. (Université McGill, 1992)
Keywords: Banlieue; Quartiers; Saint-Henri; Sainte-Anne

Housing the Grey Nuns: Power, Religion and Women in fin-de-siècle Montréal - Martin, Tania Marie (Université McGill, 1995)
Keywords: Communautés religieuses; Couvents; Soeurs Grises

Single Room Occupancy (SRO) for Montreal’s Homeless Population - Rubial Carvajal, Isabella (Université McGill, 2016)
Keywords: Logement; Pauvreté

Building landscape narratives: the material and visual culture of bridge construction in Montreal, 1854-1930 - Braiden, Heather (Université McGill, 2021)
Keywords: Ponts; Victoria (pont)

Social Transformation in Notre Dame de Grâce over the Long Sixties - Kastner, Jeffrey (Université McGill, 2023)
Keywords: Centres d'acceuil